ASPECTOS BIOLÃ“GICOS E COMPORTAMENTAIS DE ð˜–ð˜±ð˜°ð˜¨ð˜°ð˜¯ð˜¢ ð˜´ð˜¢ð˜¤ð˜¤ð˜©ð˜¢ð˜³ð˜ª (BOJER, 1856) (LEPIDOPTERA: TINEIDAE), EM CONDIÃ‡Ã•ES DE LABORATÃ“RIO - Bergmann, Eliana Cherubini; Romanholi, Rita de Cassia; Potenza, Marcos Roberto; Imenes, Silvia de Lamonica; Zorzenon, Francisco JosÃ©; Rodrigues Netto, Sandra M. (REVISTA DE AGRICULTURA, 2020)
ASPECTOS BIOLÃ“GICOS E COMPORTAMENTAIS DE ð˜–ð˜±ð˜°ð˜¨ð˜°ð˜¯ð˜¢ ð˜´ð˜¢ð˜¤ð˜¤ð˜©ð˜¢ð˜³ð˜ª (BOJER, 1856) (LEPIDOPTERA: TINEIDAE), EM CONDIÃ‡Ã•ES DE LABORATÃ“RIO